The Affecting Factors of Stunting in Tarus Primary Health Care, Central Kupang Sub-District, Kupang Regency - Zita Apriliani Jeche; Intje Picauly; Tadeus A.L Regaletha (Lontar : Journal of Community Health, 2023)
Stunting is a condition of failure to thrive as a result of chronic malnutrition in children under five. In 2018, Kupang Regency was one of the districts that was included in the priority area for handling stunting with 34.5% stunting cases, the highest being in the working area of ​​the Tarus Health Center, which has 306 stunting toddlers. This study aims to determine the factors that influence the incidence of stunting in working area of ​​the Tarus Health Center. This type of research is an analytic survey with a case control study design. The number of samples was 150 children under five who were selected by systematic random sampling. Data collection was done by means of observation and structured interviews using a questionnaire. Data analysis was performed using chi-square test (bivariable) and multiple logistic regression (multivariable) with (a) = 0.05. The results showed that the factors which influenced the incidence of stunting were the level of parental income (p= 0.014), the level of knowledge at maternal nutrition (p= 0.011), big family (p= 0.022), feeding practices (p= 0.011), the level of nutritional adequacy energy (p= 0.033), and protein adequacy level (p= 0.000). The dominant factors of stunting that have the most influence are the level of protein adequacy, the level of parental income, feeding practices, and big family. From the results of the study, it is hoped that health workers can provide nutritional counseling to mothers under five so that the information obtained can be remembered and practiced well.